2023
DOI: 10.4102/sajim.v25i1.1539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social trust on health information exchange in social network sites

Abstract: Objectives: This study investigates the nature of the association between health information exchange and social trust and how social trust has influenced health information exchange from 2005 to 2021. Method:In line with the purpose of the study, the researcher applied a systematic literature review to review conference articles, accredited journal articles and book chapters. The review process involved a rigorous procedure towards a definition of review protocol, extraction of articles, formulation of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Numerous studies have explored the relevance of social media platforms to epidemiological patterns and medical information. 18 For instance, even before the COVID-19 pandemic, research suggested a strong correlation between the regional distribution of social media posts related to infectious diseases and their actual spread. 19 Additionally, studies on trend analysis using search queries have shown associations with the spread of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the relevance of social media platforms to epidemiological patterns and medical information. 18 For instance, even before the COVID-19 pandemic, research suggested a strong correlation between the regional distribution of social media posts related to infectious diseases and their actual spread. 19 Additionally, studies on trend analysis using search queries have shown associations with the spread of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…With Facebook, Twitter, and Instagram being the most prominent sites, these social networking sites have overwhelmed the digital landscape (Sun et al, 2023;Gokalpt et al, 2023;Ng et al, 2023;Kuss & Griffins, 2022). Instant messaging servicessuch as Snapchat, WhatsApp, Facebook, etc.have recently reached a substantial part of the user base (Musetti et al, 2022;Mkhize, 2023;Pew, 2018). Social media users can upload or stream intimate content for others to react, share, and respond to; lastly, vlogging sites i.e., YouTube, is also widely popular among youth (Kuss & Griffins, 2022;Verduyn et al, 2022;Pew, 2018;Valkenberg, 2022).…”
Section: Introductionmentioning
confidence: 99%